2023
DOI: 10.4081/aiua.2023.11084
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of effect of standard antibiotic prophylaxis versus enhanced prophylactic measures on rate of urinary tract infection after flexible ureteroscopy

Abstract: Purpose: To compare the rate of post-flexible ureteroscopy urinary tract infection (UTI) in patients subjected to the standard antibiotic prophylaxis alone versus enhanced prophylactic measures. Methods: A prospective randomized controlled study included 256 patients subjected to flexible ureteroscopy (FURS) for ureteral or renal stones from March 2018 to July 2022. Treatment groups included the standard antibiotic prophylaxis group (group 1, n=128) and the enhanced prophylaxis group (group 2, n=128). Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We reported a 22.3% rate of postoperative UTIs occurring in patients who underwent endoscopic procedure, which is consistent with rates in similar studies reported by Mitsuzuka et al (18.3%) [31] and by El-Agamy et al (15.6%) [29]. In the univariable logistic regression analysis, several factors associated with postoperative UTI, including stone diameter, number of stones, type of ureterorenoscope (multi-use vs. single-use), and operative time, were evaluated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We reported a 22.3% rate of postoperative UTIs occurring in patients who underwent endoscopic procedure, which is consistent with rates in similar studies reported by Mitsuzuka et al (18.3%) [31] and by El-Agamy et al (15.6%) [29]. In the univariable logistic regression analysis, several factors associated with postoperative UTI, including stone diameter, number of stones, type of ureterorenoscope (multi-use vs. single-use), and operative time, were evaluated.…”
Section: Discussionsupporting
confidence: 92%
“…The interaction between urinary stones and bacterial colonization provides a fertile ground for the development of UTIs, as the presence of calculi can lead to urinary stasis, obstruction, and mucosal trauma, predisposing patients to microbial ascent and infection [27,28]. Recent studies in line with those reported from the EAU guidelines [17] offer valuable insights into the management of UTIs in urological practice, emphasizing the importance of risk stratification, perioperative antibiotic prophylaxis, and tailored antimicrobial therapy based on local resistance patterns and patient-specific factors [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…40 Urine culture is not mentioned in European Guidelines. Its role in the prevention of UTIs has been analyzed by El-Agamy et al 79 A randomized comparison was performed between standard AP and enhanced prophylactic measures using urine cultures and targeted pharmacological therapy. Results demonstrated that an antibiotic-culture-based therapy could significantly reduce the risk of UTIs in patients undergoing ureteroscopy when compared with a traditional empirical antibiotic.…”
Section: Ureteroscopy and Endoscopic Lithotripsymentioning
confidence: 99%
“…Five studies were identified [26,49,50,51 ▪▪ ,52 ▪ ] of which only two had greater than 500 participants [51 ▪▪ ,52 ▪ ].…”
Section: Urological Surgerymentioning
confidence: 99%
“…Five studies were identified [26,49,50 ]. The Urological Infections Guideline Group of the European Association of Urology (EAU) guidelines were recently updated [66] and highlight the preference for transperineal prostate biopsy (TPPB) over transrectal (TRPB) where possible due to lower infectious rates [66].…”
Section: Urological Surgerymentioning
confidence: 99%